Corporate strategy formulation af a University in England an application of the repertory grid technique - Siti Maimon Kamso,; Wan Rafaei,; R. E. Thomas, (Penerbit Universiti Kebangsaan Malaysia, 1984)
This article looks into a fornudation of Corporate Strategic Planning (CSP) in a public organisation, viz, a university in England. The Twiss's CSP fornulation Model (1976) was applied. It took into account the interrelationship of the objectives, the strengths and weaknessess and opportunities and threats (SWOT), and the alternative strategies simultaneously in a strategic choice formulation. The ethos, style and mind of top management which were embodied in the subject of the study were also impregnated in the simuhaneous consideration. A set of questionnaires were administered to the subject, i.e., one of the 3 high ranking officials of the university who formed the top management team in the Corporate Strategic Planning of the university whose office therefore enabled him to perceive clearly the future directions of the ILniversity and its objectives and policies. The elicited and supplied SWOT factors and numerous strategies were put in the Repertory Grid far scoring. The results were then analysed with the use of Grid Analysis Package (the INGRID Program). This is the first time that an applic-ation of this technique is used in the strategic: choice of a CSP formulation. The findings indicated clearly the order of the priority of the alternative strategies of the university, as represented in the corporate Strategy Mental Map (Mm). Clear representation of the conceptualised strategies and their interelationships with the SWOT factors were also shown, in the cognitive map, thus showing the Repertory Grid Technique as a potentially useful tool in CSP analysis.